Immunohistochemical expression of androgen receptor in cutaneous basal cell carcinoma - Bartoš, Vladimír; Kullová, Milada (Journal of Pakistan Association of Dermatologists, 2019)
Background Androgen receptor (AR) is known to be expressed in a variety of skin tumors, including basal cell carcinoma (BCC). The aim of this study was to investigate an expression status of AR by immunohistochemistry in a set of cutaneous BCC. Â Material and Methods The study group consisted of 54 BCCs from 49 patients. Based on histomorphology, BCC subtypes were merged into non-aggressive (superficial and nodular subtypes) and aggressive (nodular-infiltrative and infiltrative subtypes) subgroups. Specific monoclonal antibody against AR was used for immunostaining. Â Results AR was expressed in 32 BCCs (59.3%). In superficial, nodular, nodular-infiltrative and infiltrative BCC subtypes, nuclear reactivity for AR was found in 70% (7/10), 73.1% (19/26), 35.7% (5/14) and 25% (1/4), respectively. A wide quantitative range of AR expression (1â€“90% of tumor tissue) was seen. There were twenty-seven cases (84.4%) with focal staining and five cases (15.6%) with diffuse staining. There was significantly lower rate of AR expression in BCCs exhibiting aggressive histomorphologic phenotype. No correlation between AR expression and anatomic location and gender was found. Â Conclusion Although cutaneous BCC is generally considered to be AR-positive neoplasm, in the present study, immunoreactivity for AR was detected only in about half of the cases. Most AR-positive tumors showed only focal staining. The pathologists should be aware of these findings, which may cause difficulties in distinguishing BCC from related AR-negative epithelial skin tumors. Â